2009
DOI: 10.1080/08952840802633669
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Built Environment and Other Factors on the Physical Activity of Older Women from Different Ethnic Communities

Abstract: Inactivity has been identified as a major contributor to the burden of disease in older women. Study aims were: (a) to assess the personal, social, and environmental facilitators and impediments to physical activity in older women from ethnic communities; and (b) to determine the factors associated with physical activity participation. Older women (aged 60-84 years) were recruited from the local Italian (n = 20), Vietnamese (n = 26) and Anglo-Celtic (n = 26) communities. A survey questionnaire was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…For example, in a study of older people (M = 72 years) from seven different cultural groups there was no difference found between the reported amount of physical activity by men and women indicating that gender was not a significant correlate of physical activity in this population [51]. Being unmarried [53,54] or living alone [55] was associated with higher levels of physical activity for women. Furthermore, one study found that rural women were less physically active than urban women [56].…”
Section: Demographicmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, in a study of older people (M = 72 years) from seven different cultural groups there was no difference found between the reported amount of physical activity by men and women indicating that gender was not a significant correlate of physical activity in this population [51]. Being unmarried [53,54] or living alone [55] was associated with higher levels of physical activity for women. Furthermore, one study found that rural women were less physically active than urban women [56].…”
Section: Demographicmentioning
confidence: 91%
“…Specific motivators for engaging in sports and physical activity differed according to cultural group, but some common motivators included maintaining physical health [44,68,75], managing chronic disease A review of sport and physical activity in culturally and linguistically diverse migrants 14 [76,77] and socialising [55,58,77]. Generally, the greater the number of motives an individual cited, the greater was their participation in sports and physical activity [37,65].…”
Section: Psychosocialmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical disorder-the deterioration of urban landscapes [8]-may be an important and modifiable barrier to physical activity, particularly walking, among older adults [9][10][11][12]. However, the quantitative evidence base that physical disorder acts as such a barrier is limited.…”
Section: Introductionmentioning
confidence: 99%
“…To assess engagement in different PA domains and total PA, the International Physical Activity Questionnaire (IPAQ, long form, last 7 days, interview version) was adapted (a separate question targeting cycling for recreation was added) and used. The IPAQ has been validated in older adults (Hurtig-Wennlof, Hagstromer, & Olsson, 2010) and has been used in several previous studies in older adults (Berke, Koepsell, Moudon, Hoskins, & Larson, 2007;Bird, et al, 2009;Salvador, et al, 2010).…”
Section: Structured Interviewmentioning
confidence: 99%